Psychic Income Associated With Shanghai Tennis Masters and Residents’ Attitude - Zhang, Fengyun; Liu, Dongfeng; Plumley, Daniel; Chai, Mengyan (Frontiers in Psychology, 2022)
Using Shanghai Tennis Masters as an example, this study seeks to explore the psychic income associated with major sports events hosting and whether the psychic income would predict the attitudes of local residents toward events hosting. In addition, the moderating effect of sport involvement on the relationship between psychic income and attitude is also tested. In this study, a questionnaire survey is adopted. The structured questionnaire was developed based on 4 parts, including the demographics of the residents, involvement in the sport event, psychic income from the sport event, and their attitudes toward the sports event, there were 47 items in total. Data were collected from the local residents of Shanghai (including 16 districts or counties), as a result, 1,302 valid questionnaires were collected. A series of statistical analyses were conducted by using SPSS25.0 and AMOS 24.0 to examine the reliability and validity of the scales and to test the hypotheses. The results showed that the event has brought a significant level of psychic income to the local community, and the perceived psychic income would predict the attitudes of the residents toward the event hosting. The moderating effect of sports involvement on the relationship between psychic income and attitude is also confirmed.